Age-Related Changes in Sensorimotor Temporal Binding - Vercillo, Tiziana; Carrasco, Carlos; Jiang, Fang (Frontiers in Human Neuroscience, 2017)
The causal relationship between a voluntary movement and a sensory event is crucial for experiencing agency. Sensory events must occur within a certain delay from a voluntary movement to be perceived as self-generated. Therefore, temporal sensitivity, i.e. the ability to discriminate temporal asynchronies between motor and sensory events, is important for sensorimotor binding. Moreover, differences in the physical propagation of external stimuli can sometimes challenge sensorimotor binding, generating illusory asynchrony. To overcome this problem, the brain adjusts the perceptual timing of sensory and motor events. This mechanism, named sensorimotor recalibration, helps keeping causality judgments accurate. As humans age, the broad decline in sensory and motor processing may reduce temporal sensitivity, and compromise sensorimotor recalibration. In the current study, we investigated the effect of aging on sensorimotor temporal binding by measuring changes in both temporal sensitivity and recalibration. Young and elderly adults were exposed to a prolonged physical delay between a voluntary movement (a keypress) and its perceptual consequence (a visual stimulus). Before and after this exposure, participants performed a sensorimotor temporal order judgement task. As expected, elderly adults showed reduced sensorimotor recalibration and sensitivity as compared to young adults, suggesting that aging affects sensorimotor temporal binding.